A More Extensive Lymphadenectomy Enhances Survival After Neoadjuvant Chemoradiotherapy in Locally Advanced Esophageal Adenocarcinoma. Issue 2 (17th August 2022) - Sihag, Smita; Nobel, Tamar; Hsu, Meier; Tan, Kay See; Carr, Rebecca; Janjigian, Yelena Y.; Tang, Laura H.; Wu, Abraham J.; Bott, Matthew J.; Isbell, James M.; Bains, Manjit S.; Jones, David R.; et al.
Abstract : Objective: We sought to determine the extent of lymphadenectomy that optimizes staging and survival in patients with locally advanced EAC treated with neoadjuvant chemoradiotherapy followed by esophagectomy. Summary of Background Data: Several studies have found that a more extensive lymphadenectomy leads to better disease-specific survival in patients treated with surgery alone. Few studies, however, have investigated whether this association exists for patients treated with neoadjuvant chemoradiotherapy. Methods: We examined our prospective database and identified patients with EAC treated with neoadjuvant chemoradiotherapy followed by esophagectomy between 1995 and 2017. Overall survival (OS) and DFS were estimated using Kaplan-Meier methods, and a multivariable Cox proportional hazards model was used to identify independent predictors of OS and DFS. The relationship between the total number of nodes removed and 5-year OS or DFS was plotted using restricted cubic spline functions. Results: In total, 778 patients met the inclusion criteria. The median number of excised nodes was 21 (interquartile range, 16–27). A lower number of excised lymph nodes was independently associated with worse OS and DFS (OS: hazard ratio, 0.98; confidence interval, 0.97–1.00; P = 0.013; DFS: hazard ratio, 0.99; confidence interval, 0.98–1.00; P = 0.028). Removing 25 to 30 lymph nodes was associated with a 10% risk of missing a positive lymph node. Both OS and DFS improved with up to 20 to 25 lymph nodes removed, regardless of treatment response. Conclusions: The optimal extent of lymphadenectomy to enhance both staging and survival after chemoradiotherapy, regardless of treatment response, is approximately 25 lymph nodes.